Deciphering the role of Wnt/β-catenin and miR-214 in knee osteoarthritis: molecular and clinical insights - Samman, Waad A.; Mosalam, Esraa M.; Saif, Dalia S.; Abdallah, Mahmoud S.; Zidan, Abdel-Aziz A.; Sallam, Amany Said; Abdelsattar, Shimaa; Khalil, Fatma Omar; Elashkar, Amany E.; Mohamed, Somia Mokabel; Al-Ghannam, Mohamed; Abo Mansour, Hend E. (Frontiers in Pharmacology, 2025)
IntroductionUnderstanding the molecular mechanism underlying the pathogenesis of knee osteoarthritis (KOA) may be beneficial in fetching new therapeutics. Our study aims to investigate the implication of Wnt/ β-catenin pathway in development of KOA by detection of the downstream target genes and their crosstalk with miR-214 in patients with KOA and to correlate that with the clinical findings.MethodsSixty participants were involved in the study. The levels of miR-214, β-catenin, Wnt4, matrix metalloproteinase 3 (MMP3), Bax, caspase 3, and phosphorylated glycogen synthase kinase-3 beta (pGSK3β) were determined. All participants were assessed clinically and radiologically regarding knee joint pain, stiffness, range of motion, and knee medial cartilage thickness. Besides, a correlation between Western Ontario and McMaster Universities (WOMAC) score, clinical, and radiological data, and the measured parameters was conducted.Results and discussionPatients with KOA showed downregulated miR-214 with upregulated β-catenin, Wnt4, MMP3, Bax, caspase 3, and pGSK3β compared to healthy individuals. Statistically significant positive correlation between WOMAC score, knee joint pain regarding Visual Analogue Scale (VAS) with β-catenin, pGSK3β, Wnt4, MMP3, Bax, and caspase 3, and significant negative relationship between them and knee joint medial cartilage thickness; while there was a statistically significant negative correlation between WOMAC, and clinical findings of osteoarthritis and miR-214 and significant positive relationship between it and knee joint medial cartilage thickness. This study provides valuable insights into involvement of the Wnt/β-catenin and miR-214 in KOA pathogenesis. By targeting these molecular components, future therapeutics may modulate their activity and mitigate chondrocyte apoptosis and matrix degradation, potentially halting KOA progression.